2018
DOI: 10.4269/ajtmh.17-0992
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Lee–White Clotting Time Performed in the Hospital Routine to Detect Coagulopathy in Bothrops atrox Envenomation

Abstract: Snake envenomation is a major public health problem in Brazil. Systemic complications that may arise from snakebites are mainly related to coagulopathy. The Lee-White clotting time (LWCT) is a simple and inexpensive test and available even in remote health facilities. However, the diagnostic value of such test needs to be evaluated to accurately diagnose coagulopathy in the clinical practice. This study aimed to assess the reliability of the LWCT performed in hospital routine to diagnose venom-induced coagulop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Those results suggest at least a partial efficacy of AV Antivipmyn Tri ® to reverse coagulation disorders after SB without a strong difference between the two dosage regimens used. A recent study on the use of the same antivenom in snake-bitten patients attended to in the Guianese western hospital did not reveal differences in the time needed to restore coagulation parameters between patients receiving three vials of antivenom and patients that did not receive antivenom [ 20 ]. The reasons for this discrepancy remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those results suggest at least a partial efficacy of AV Antivipmyn Tri ® to reverse coagulation disorders after SB without a strong difference between the two dosage regimens used. A recent study on the use of the same antivenom in snake-bitten patients attended to in the Guianese western hospital did not reveal differences in the time needed to restore coagulation parameters between patients receiving three vials of antivenom and patients that did not receive antivenom [ 20 ]. The reasons for this discrepancy remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of lethal activity, Antivipmyn Tri ® did not neutralize the effect at the highest antivenom level tested (1 mg venom/mL antivenom). A previous study indicated that the dose of three vials is insufficient, especially in grade 2 or 3 cases, since no improvement in the correction of coagulation parameters was observed [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compartment syndrome was diagnosed by an experienced physician by serial physical examinations and intramuscular pressure measurement. Coagulopathy was defined as an unclottable blood from the Lee-White clotting time method [6]. Patients were treated according the Brazilian Ministry of Health protocols.…”
Section: Patientsmentioning
confidence: 99%
“…Three applied tourniquets at the bitten limb. All patients presented edema (14), followed by pain (13) and local bleeding (6). One patient developed blistering, and 4 evolved to secondary infection after 48 hours of follow-up (3 with abscess and 1 with cellulitis) and 2 had necrosis.…”
Section: Patients' Signs and Symptomsmentioning
confidence: 99%
See 1 more Smart Citation